2001
DOI: 10.1183/09031936.01.00089501
|View full text |Cite
|
Sign up to set email alerts
|

How should airways resistance be measured in young children: mask or mouthpiece?

Abstract: The reproducibility and acceptability of airways resistance measurements using the interrupter technique (MicroRint) obtained using a mouthpiece were compared with those using a face mask.Fifty children aged 4 -7 yrs performed four sets of six Rint measurements; two using a mouthpiece and two using a face mask with integral mouthpiece.Complete data were obtained from 45 (90%) children using the mouthpiece and 43 (86%) children using the mask. The two methods were equally repeatable with comparable intraclass c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…The use of face masks in children v3 yrs may enhance the feasibility of the test, but Rint measurements obtained using face masks can differ from those obtained with mouthpieces [21] due to differences in the compliance and resistance of the mask and the degree of airways obstruction. Rint measurements using face masks may require specific reference equations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of face masks in children v3 yrs may enhance the feasibility of the test, but Rint measurements obtained using face masks can differ from those obtained with mouthpieces [21] due to differences in the compliance and resistance of the mask and the degree of airways obstruction. Rint measurements using face masks may require specific reference equations.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,32 Al igual que otros trabajos previos, 4,6,[17][18][19]21,28 no hay diferencias significativas entre las medidas, lo que indica que la fiabilidad de la técnica es adecuada, similar a la de otras técnicas de medición de resistencias. 26 En un estudio previo 33 se encontraron diferencias pequeñas entre las mediciones con boquilla y mascarilla, por lo que se prefirió el uso de mascarilla. Esta medida no mejoró la reproducibilidad e insumió más tiempo en cada medida.…”
Section: % Fev1unclassified
“…4,5,32 As with other previous studies, 4,6,[17][18][19]21,28 no significant differences were observed among measurements, indicating that the technique is adequately reliable, as the other techniques to measure resistances. 26 One previous study 33 found small differences in measurements obtained with a mouthpiece and a mask; for this reason, the mask was chosen, but did not improve reproducibility and it took longer to obtain each measurement. In our study, no significant differences were observed between both types of measurements, so it appears that there are no sufficient data to favor one method over the other.…”
Section: Figure 3 Correlation Between the Difference Of The Resistanmentioning
confidence: 99%